Breakthrough Conductivity Enhancement in Deep Eutectic Solvents via Grotthuss‐Type Proton Transport - Desiree Mae Prado; Alan Robledo; Katherine Hightower; Anthony Jahng; Brian Doherty; Kayla Poling; Mark Tuckerman; Clemens Burda (Advanced Materials Interfaces)
Abstract There is an increasing demand for the development of ion‐conducting electrolytes for energy storage systems. Much attention is directed toward deep eutectic solvents as potential candidates. In the search for highly conductive systems, the possibility of designing deep eutectic solvents with Grotthuss‐type proton transport is widely overlooked. Herein, ethaline, a mixture of choline chloride and ethylene glycol is used in a 1:2 molar ratio, to induce a significant conductivity increase with the addition of water and sulfuric acid (H2SO4). The achieved breakthrough conductivity is analyzed experimentally and simulated with ab initio molecular dynamics (AIMD). At sufficient water content, an H‐bonding network is formed that leads to a significant breakthrough conductivity based on H2SO4‐derived proton transfer following the long‐established Grotthuss proton transport mechanism. This result is substantiated by the positive deviation from the ideal KCl line in the Walden plot. Specifically, the data series positioned above the reference line indicates a Grotthuss mechanism in action. The AIMD simulations demonstrate proton transfer between water and ethylene glycol, supported by simulation frames captured at various times.